x(t) = -u(t-3)+2u​(t+1)-2u(t​-1)+u(t-3)

60 Ansichten (letzte 30 Tage)
cadburry oreo
cadburry oreo am 4 Okt. 2020
Beantwortet: Jonas am 8 Feb. 2023
x(t) = -u(t-3)+2u(t+1)-2u(t-1)+u(t-3)
how to solve it ? help i'm new

Antworten (1)

Jonas
Jonas am 8 Feb. 2023
please check your given equation, the last and first term cancel out each other. Nevertheless, i kept both of them in the code below
generate a time vector from -5 to 5 with step 0.1
t=-5:0.1:5;
generate unit step data
x=zeros(size(t));
preFactors=[-1 +2 -2 +1];
timeShifts=[-3 +1 -1 -3];
for termNr=1:numel(preFactors)
% create current unit impulse
thisTerm=t>-timeShifts(termNr);
% add up
x=x+preFactors(termNr)*thisTerm;
end
stem(t,x,'.')

Kategorien

Mehr zu Systems of Nonlinear Equations finden Sie in Help Center und File Exchange

Tags

Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!

Translated by